How degraded is our DNA? A review of single source live case work samples with optimal DNA inputs processed with the PowerPlex® ESI17 Fast kit. (December 2015) - Moore, D.; Thomson, J.
Abstract: LGC validated the PowerPlex ® ESI17 Fast system (ESI17F), (Promega) in July 2014. As part of the validation a characterisation study was performed to assess kit performance at different DNA inputs. Following implementation of the ESI17F system, reports of lower than expected peak heights and heterozygous imbalance being present in optimal input (500 pg) samples were made. A review of profile quality for single source samples with optimal DNA input was carried out. A number of variables were assessed to see if there was a connection with the observed reduced peak height and heterozygous events. Sample degradation was observed to be the major cause of reduced peak heights and heterozygous imbalance in samples with optimal DNA input. Evidence of DNA degradation was observed in ∼50% of samples reviewed. Although the ESI17F system provides smaller amplicons for the loci that are required to load to the UK National DNA database; the larger number of loci present within the kit results in a larger number of large amplicons that are more likely to be affected by DNA degradation.